Nonhuman animals and the future of environmental education: Empathy and new possibilities. Issue 4 (2nd December 2019) - Dolby, Nadine
ABSTRACT: Similar to other fields, environmental education has begun to embrace the significance of nonhuman animals. This essay examines developments in the natural sciences, particularly in the field of cognitive ethology, that focus on the concept of empathy as a paradigm for conceptualizing human/nonhuman animal relationships. Drawing on my own experience using this model of empathy in a course focused on animals, society, and education, I suggest ways that environmental education can incorporate these new understandings about nonhuman animal sentience, cognition and emotion into the field.